2014
DOI: 10.1002/pssr.201409011
|View full text |Cite
|
Sign up to set email alerts
|

Surface treatment of electrodeposited n‐type Cu2O thin films for applications in Cu2O based devices

Abstract: In this Letter, we report the effects of ammonium sulfide [(NH4)2S] surface treatment on electrical and optical characteristics of the electrodeposited n‐type Cu2O thin films on Ti substrates. Films characterized structurally and morphologically before and after the surface treatment were compared using conductivity, spectral photoresponse and current–voltage (I–V) measurements. The ammonium sulfide surface treatment time showed an impact on optical and electrical characteristics of the films. Treated Cu2O fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
27
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 21 publications
3
27
0
Order By: Relevance
“…Some of the key issues that need to be addressed in Cu 2 O thin film solar cell development is the associated high resistivity and defects of the Cu 2 O thin films. For device applications, especially, the minimization of surface defects such as those due to dangling bonds and nonradiative recombination centers in the Cu 2 O films is of utmost importance because it causes to reduce resistivity and enhance the electrical and optical properties . An obvious approach to modify surface and interface properties of semiconductors is to make the surface interact with foreign atoms, e.g., sulfur , selenium , chlorine , or simple radicals, e.g., cyanides .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the key issues that need to be addressed in Cu 2 O thin film solar cell development is the associated high resistivity and defects of the Cu 2 O thin films. For device applications, especially, the minimization of surface defects such as those due to dangling bonds and nonradiative recombination centers in the Cu 2 O films is of utmost importance because it causes to reduce resistivity and enhance the electrical and optical properties . An obvious approach to modify surface and interface properties of semiconductors is to make the surface interact with foreign atoms, e.g., sulfur , selenium , chlorine , or simple radicals, e.g., cyanides .…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted by us on passivation of n‐Cu 2 O and p‐Cu 2 O thin films using ammonium sulfide have demonstrated that the film resistivity can be lowered while increasing the photoactivity of the related thin film solar cell structures. It was shown that the increase in the peak photocurrent was approximately a 50‐fold and 4‐fold, respectively, compared to the untreated n‐type Cu 2 O and p‐type Cu 2 O films . The passivation along with annealing was successfully used to improve the efficiency of Ti/p‐CuO/n‐Cu 2 O/Au solar cell.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, In 2 S 3 /Cu 2 O35 and ZnO/Cu 2 O36 interfaces have been found to be promising for photovoltaic applications. From the experimental point of view, the electrical resistivities of a Cu 2 O thin film between two gold leads using SiO 2 /Si substrates37, and of a sulfur-treated n-type Cu 2 O thin film with Ag, Cu, Au, or Ni front contacts have been measured38. However, very little is known about the theoretical understanding of electronic transport properties of heterojunctions involving Cu 2 O.…”
mentioning
confidence: 99%
“…The 20 original Letters present exciting new research on the topics of transport properties [4], super-reducible oxides [5], ferroelectricity [6], point defects [7], memory applications [8][9][10], bulk properties [11][12][13][14], interfaces [15][16][17], surfaces [18][19][20] and catalytic properties [21][22][23].…”
mentioning
confidence: 99%